Reflexões críticas em torno de Rubén Darío: relendo as interpretações de José Enrique Rodó e de Manuel Gondra - Elisângela da Silva Santos (Universidade do Vale do Rio dos Sinos (UNISINOS), 2019)
This article aims to retake two criticisms made to the book Prosas profanas y otros poemas, by Nicaraguan poet Rubén Darío (1867-1916), criticisms that were written by Manuel Gondra (1871-1927) and José Enrique Rodó (1871- 1917). Both of the analyses, published at the end of the 19th century, questioned the absence of themes characteristic of the America in that production by Darío, recognized as the most outstanding poet of the moment. Rubén Darío, José Enrique Rodó and Manuel Gondra, will be read as authors who helped in the insertion of literary and cultural expressions of their countries, from the Hispanic-American movement of modernism, they searched for narrative, cultural and artistic paths, in the midst of the consolidation process of their Nation-States. The conception of literature brought by critics in relation to Darío can be seen as constitutive of the social and cultural process, which formulated broader social projects. In this sense, we observe that the Latin Americanist rhetoric was in search of an aesthetic model that could elect, protect and forge the materials of our identity.